Respuesta :

Answer:

A and D

Step-by-step explanation:

Since we cannot factor using factored form, we need to use the quadratic formula.

When we plug it in using the values :

a = 1

b = -5

c = 3

We get

x = (5+-sqrt(13))/2

Which is answer choices A and D.

The two values of x that are roots of this equation x²-5x+3=0 are x = [tex]\frac{5+\sqrt{13} }{2}[/tex]and  x = [tex]\frac{5-\sqrt{13} }{2}[/tex]. This can be obtained by using formula to find roots of quadratic equation.

What is the formula to find roots of quadratic equation?

For a quadratic equation ax²+bx+c = 0,

the roots are obtained using the formula, [tex]x =\frac{-b+\sqrt{b^{2}-4ac } }{2a}[/tex]  and

[tex]x =\frac{-b-\sqrt{b^{2}-4ac } }{2a}[/tex]

Find the two values of x:

Given that the quadratic equation is x²-5x+3=0

⇒a = 1, b= - 5, c = 3

By using the formula to find roots of quadratic equation the roots are,

[tex]x =\frac{-(-5)+\sqrt{(-5)^{2}-4(1)(3) } }{2(1)}[/tex] and [tex]x =\frac{-(-5)-\sqrt{(-5)^{2}-4(1)(3) } }{2(1)}[/tex]

[tex]x =\frac{5+\sqrt{25-12 } }{2}[/tex] and [tex]x =\frac{5-\sqrt{25-12 } }{2}[/tex]

[tex]x =\frac{5+\sqrt{13 } }{2}[/tex] and [tex]x =\frac{5-\sqrt{13 } }{2}[/tex]

These are the required roots.

Hence the two values of x that are roots of this equation x²-5x+3=0 are x = [tex]\frac{5+\sqrt{13} }{2}[/tex]and  x = [tex]\frac{5-\sqrt{13} }{2}[/tex].

Therefore the correct answer is option A. and option D.

Learn more about solving quadratic equations here:

brainly.com/question/1214333

#SPJ2